Care of caregivers – who is responsible? - Karpaga, Priya P; Padhy, Gouri Kumari; Kumar, Mohan (Indian Journal of Community Health, 2021)
Demographic and epidemiologic transition coupled with increasing life expectancy has resulted in high old age dependency ratios and rising burden of comorbidities; especially non communicable diseases. This demands large pool of caregivers to support the dependents; physically, psychologically and financially. But the problems faced by caregivers – stress, anxiety, monetary, physical exhaustion and sickness, lack of time for personal care and health resulting in caregiver burden – is often neglected. This article summarizes the importance and/or role of caregivers, theirs problems and recommendations to identify, manage and prevent caregiver burden. The involvement of various stakeholders namely medical and para-medical colleges through training and medical education, hospitals, physicians, psychiatrists and/or psychologists, research organizations, governments and their policies is the need of the hour.